Presumed Protective Role for Anti-Hepatitis B Virus Antibodies Against COVID-19 Severe Cases: A Clinical Study Confirming in silico Hypothesis - Gdoura, Mariem; Touati, Raoua; Kalthoum, Sana; Ben Slama, Rania; Fatnassi, Nouel; Mrad, Mehdi; Ammari, Lamia; Brahmi, Nozha; Ben Jazia, Amira; Hogga, Nahed; Triki, Henda; Haddad-Boubaker, Sondes (Frontiers in Medicine, 2022)
Background Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is responsible for COVID-19 disease which is known to have a broad clinical spectrum, from asymptomatic to critical presentation leading to death. Many researchers have investigated the factors impacting the course of the disease. Our previous in silico study suggested a possible protective effect of Hepatitis B, Tetanus and Measles vaccines against COVID-19. In continuity, we conducted a cross-sectional clinical study in order to confirm our in silico assumptions regarding the HBs-Ag antibodies. Methods A representative sex- and age-matched sample of patients with confirmed COVID-19 was selected (n = 340). All clinical presentations were equally represented. Using an ELISA test, each patient benefited of a serology for the detection and measurement of the anti-HBs specific IgG antibodies. The obtained results allowed determining the different correlations between these antibody titers and the disease severity. The R® software and the MedCalc® software served to calculate the Spearman's coefficient of rank correlation (rho) for the obtained titers per severity group as well as the different other calculations and figure representations. Results A significant positive correlation was found with the anti-HBs titers (rho = 0.107; p = 0.04). High anti-HBs titers were significantly associated with the mild presentation of COVID-19. A significant difference was found between the obtained titers per severity class (chi-2 test, p = 0.03). Discussion/Conclusion Our findings demonstrated that anti-HBs titers were significantly higher for patients having mild COVID-19 presentations. We presume that being immunized against the HB may play a protective role in the course of the disease. Our study provided more key elements in understanding the disparity of the clinical spectrum among regions.